2015
DOI: 10.4314/gjpas.v21i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Perception and attitudes of parents towards teenage pregnancy in a rural community of Cross river state, Nigeria

Abstract: Teenage pregnancy is a social menace and common public health problem. It is detrimental to both mother and child because teenage mother is not physically, psychologically and economically ready to bear a child. This phenomenon has multiple adverse consequences on maternal health, child health and overall wellbeing of the society. This study investigated the perception and attitudes of parents towards teenage pregnancy in a rural community in Akpabuyo Local Government Area. The objectives included: to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…On the other hand, in addition to participants' expression of sexual behaviours and tendencies to have sexual life, another external pressure from the parents and other relatives perhaps increases the risk of having marriage due to the parent's belief that the girl is old enough to get married. For the sake of their morale and the culture of the society, they can force girls with the idea of marrying and to prevent giving birth to a girl out of wedlock [ 24 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in addition to participants' expression of sexual behaviours and tendencies to have sexual life, another external pressure from the parents and other relatives perhaps increases the risk of having marriage due to the parent's belief that the girl is old enough to get married. For the sake of their morale and the culture of the society, they can force girls with the idea of marrying and to prevent giving birth to a girl out of wedlock [ 24 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In CRS (as in other parts of Nigeria and in the global context), where fertility is highly valued within the institution of marriage, unmarried young mothers often endure additional stigma and discrimination within their communities and families due to an early, unplanned, and unwanted pregnancy. [9][10][11] As a result, they may experience adverse social consequences such as curtailment of their education, decreased mobility, financial deprivation, and increased social isolation. 9,12 Young men who unexpectantly become fathers for the first time may also face numerous challenges in continuing their education and providing adequate financial support for themselves and their new family.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with what Fernandes et al [35] said that the news of teenage daughter's pregnancy is unpleasant to parents. Mgbokwere, Esienumoh and Uyana [39] in their study, confirmed that parents' negative attitudes toward teenage pregnancy affect the girl in such a way that parents stop her education, the girl is sent away from the family and the girl is abandoned to the man/boy responsible for the pregnancy. Findings also showed that parents' unpleasant reaction towards teenage pregnancy affect their educational aspirations.…”
Section: Discussionmentioning
confidence: 60%
“…Mgbokwere, Esienumoh and Uyana [39] investigated on the perception and attitudes of parents towards teenage pregnancy in a rural community in Akpabuyo Local Government Area. The objectives included: to determine parents' perception on teenage pregnancy and to determine parents' attitudes towards teenage pregnancy.…”
Section: Parents' Reaction To Teenage Pregnancymentioning
confidence: 99%